ОПРЕДЕЛЕНИЕ МИКРОЭЛЕМЕНТНОГО СОСТАВА НЕКОТОРЫХ МИНЕРАЛЬНЫХ ВОД ГРУЗИИ - Гогичаишвили Бела Арменовна; Дидбаридзе Изольда Сардионовна; Брегадзе Нестан Левановна; Махвиладзе Маиа Гелановна (World Science, 2019)
Among the chemical elements contained in small quantities in mineral waters, of interest are trace elements that have a certain biological activity. According to the method developed by us, the content of copper, nickel, zinc, cobalt, chromium and manganese in certain mineral waters of Western Georgia was determined. The obtained data on the content of trace elements in mineral waters are of practical value, information about the trace element composition will contribute to the further study of these waters in hydrogeological, hydrochemical and balneological aspects.